2019
DOI: 10.9734/ajee/2019/v9i130085
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Carbon Dioxide Variations in Selected Points in Nigeria Using Neural Network Model

Abstract: Atmospheric pollution due to carbon dioxide emission from different fossil fuels and deforestations are considered as a great and important international challenge to the societies. This study is to investigate carbon dioxide (CO2) distributions in selected points in Nigeria using neural network. Neural network model were used to estimate daily values of carbon dioxide, study spatial temporal variations of carbon dioxide, and study the annual variations of estimated and observed carbon dioxide in Nigeria. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This is in line with [17], which state that impressive performance of the neural networks model supports the application of neural network in modeling climatic parameters. Isikwue and Ibeh [18] also observed that neural network model performance were excellent and efficient in determination of spatial distribution of atmospheric parameters. The model was used to predict daily data for two years steps (2018 and 2019) ahead the period of the study for two locations.…”
Section: + +mentioning
confidence: 93%
“…This is in line with [17], which state that impressive performance of the neural networks model supports the application of neural network in modeling climatic parameters. Isikwue and Ibeh [18] also observed that neural network model performance were excellent and efficient in determination of spatial distribution of atmospheric parameters. The model was used to predict daily data for two years steps (2018 and 2019) ahead the period of the study for two locations.…”
Section: + +mentioning
confidence: 93%